การประเมินค่าตนเองและผู้อื่น: การมีส่วนร่วมในการรักษาของผู้ย้ายถิ่นที่ติดเชื้อเอชไอวี และบุคลากรทางด้านสุขภาพ - รักเหล่า ฐิติรัตน์ (Journal of Business, Innovation and Sustainability (JBIS), 2016)
งานวิจัยนี้ใช้ทฤษฎีอะเพรเซิล (Appraisal Theory) ของมาร์ตินและไวท์ (2005) ศึกษาระบบความหมายในระดับวจนะระหว่างบุคคล (Interpersonal discourse semantic system) จากลักษณะภาษาของผู้ย้ายถิ่นที่ติดเชื้อเอชไอวีและบุคลากรทางด้านสุขภาพในบทสนทนาเกี่ยวกับการรักษาและการติดเชื้อเอชไอวีในชุมชน คำถามหลักของงานวิจัยนี้คือ ผู้ย้ายถิ่นที่ติดเชื้อเอชไอวีและบุคลากรทางด้านสุขภาพมีการสื่อลักษณะภาษาการประเมินอย่างไร ถึงแม้ว่าผู้ย้ายถิ่นที่ติดเชื้อเอชไอวีส่วนใหญ่ประเมิน (Judgment) บุคลากรทางด้านสุขภาพ และแสดงความนิยม (Appreciation) ต่อการรักษาในทางบวก ผู้เข้าร่วมวิจัยกลุ่มนี้แสดงอารมณ์ความรู้สึก (Affection)ในทางลบต่อการติดเชื้อเอชไอวี โดยตระหนักถึงความเสี่ยงทางด้านสุขภาพของตนเป็นหลัก ประเด็นสำคัญประการหนึ่งในเรื่องการประเมินค่าของบุคลากรทางด้านสุขภาพต่อผู้ย้ายถิ่นที่ติดเชื้อ พบการประเมินด้านลบประเภทการยกย่องทางสังคม (Social esteem) ต่อเรื่องสถานะของผู้ย้ายถิ่นในสังคมในภาพรวมและต่อบุคคลอื่นในชุมชนอย่างเจาะจง ทฤษฎีอะเพรเซิลสามารถใช้ศึกษาการประเมินค่าของผู้เข้าร่วมวิจัยในประเด็นเรื่องการรักษาและการติดเชื้อเอชไอวีในชุมชนที่ผู้เข้าร่วมวิจัยมีส่วนร่วม อัตลักษณ์และสถานะทางสังคมตลอดจนความสัมพันธ์ระหว่างบุคคลของผู้เข้าร่วมวิจัยได้ถูกนำเสนออย่างชัดเจนในการแลกเปลี่ยนความหมาย Self and Others’ Appraisal: Engaging in Treatments of HIV infected Migrants and Healthcare Professions This study characterizes interpersonal discourse semantic system in the expression of HIV infected migrants and their healthcare professionals in the social context of the conversations about their treatments and communities by applying linguistic framework , namely, Appraisal Theory (Martin and White, 2005). This study primarily inquires: how is the language of evaluation expressed by migrants with HIV infection and healthcare professionals? Although most HIV infected migrants operate more informed judgment toward the healthcare professionals and appreciation on their treatments in the positive ways, some negative affection on the infection are revealed regarding the awareness of their own health risk. The main issue that has been raised in relation to the evaluation of healthcare professionals toward the patients is shown through the negative judgment of social esteem with regards to their status in the society as a whole, and to people in their communities in particular. Appraisal resources can used for negotiating the participants’ evaluation on treatments and communities they are engaged in. In exchanging of meaning, the participants’ social identities and positions are established, together with interpersonal relationship. DOI: http://dx.doi.org/10.14456/becj.2016.20